The role of TWEAK/Fn14 signaling in the MPTP-model of Parkinson’s disease - Mustafa, S.; Martin, H.L.; Burkly, L.; Costa, A.; Martins, M.L.; Schwaninger, M.; Teismann, P. (Neuroscience, 2016)
•We investigate the role of TWEAK and Fn14 in a model of Parkinson’s disease.•Ablation of TWEAK or Fn14 had no effect on acute MPTP toxicity.•TWEAK neutralizing antibody provided neuroprotection in the sub-acute MPTP-model.•Suggestion of a possible role for TWEAK in Parkinson’s disease. The tumor necrosis factor like weak inducer of apoptosis (TWEAK) and its receptor, fibroblast growth factor-inducible 14 (Fn14), mediate inflammation and neuronal apoptosis in cerebral edema, ischemic stroke and multiple sclerosis. The downstream effectors and pathways linked to TWEAK–Fn14 signaling are strongly implicated in the pathology of Parkinson’s disease (PD), thus indicating a putative role for TWEAK/Fn14 signaling in PD neurodegeneration. Using the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model, we aimed to determine whether genetic ablation or pharmacologic mitigation of the TWEAK protein and its Fn14 receptor affected substantia nigra and striatum Parkinsonian pathology. Changes in endogenous TWEAK protein expression were also quantified in tissue from both MPTP-treated mice and PD human samples. TWEAK protein expression was transiently increased in the striatal tissue but remained unaltered in substantia nigra tissue of MPTP-treated mice. There was also no change of TWEAK protein levels in the substantia nigra or the striatum of human PD patients as compared to matched control subjects. Mitigating the effects of endogenous TWEAK protein using neutralizing antibody did affect MPTP-mediated neurotoxicity in the substantia nigra using the sub-acute model of MPTP (30mg/kg i.p. over five consecutive days). Neither TWEAK nor Fn14 genetic ablation led to attenuation of MPTP-toxicity in the acute model. These findings suggest that TWEAK signaling might be an aspect of MPTP-mediated neuropathology and be involved in the overall neurodegenerative pathology of PD.